The recourse to drugs: Topicality of rite in our modernity (2010)
The study of the social and interindividual relationships associated with the use of the psychoactive products, frequently leads to the idea of an initiation which would fail to establish a social link. This paper reconsiders this hypothesis. For this purpose, we use the principal models in anthropology and sociology and analyze the symbolic and imaginary functions of the ritual (sacred or layman) to show all its importance within the framework of drug-addiction. The effects of drugs, as vehicles of excess, lead to the finding of an already existing Real in the human kind. In our clinical experience with drug addicts, initiation with drugs would aim, by a process of domestication that is usually compulsive and erratic, the symbolic and imaginary articulation of this Real, but also the search of a transformation in the relationship with the social Other. © 2009 Société française de psychologie. Publié par Elsevier Masson SAS. Tous droits réservés.